The cinematographic representation of epilepsy (2004-2021): A new look - Mármol, Julio (Revista Española de Comunicación en Salud, 2023)
Introduction: People with epilepsy have been represented in cinema as an outcasts and tragic characters. However, this tendency seems to be changing. Objective: To analyze the cinematographic representation of epilepsy in every film about this disease produced between 2004 and 2021. Method: Viewing and analysis of all films about epilepsy, according to IMDB, within the time period referred. Results: 1) Drama is the main genre in films about epilepsy, with strong presence of biopics. 2) USA continues to be the main country in the study sample 3) Epilepsy as a narrative function is no longer the only option, finding films where epilepsy is an arbitrary element, without actual relevance in the plot. 4) If in the film sample studied by Baxendale there were two men with epilepsy for every woman, in this analysis the male percentage decrease to 57% compared to 43% of films in which a woman suffered from epilepsy. Conclusions: The study sample reveals significative changes compared to the Baxendale´s sample, like the finding of new sensitivities about epilepsy, the emergence of films about epilepsy made to raise public awareness about the neurological disease and the increase of female characters with epilepsy.
Keywords: epilepsy; cinema; Dostoievski; disease; gender